A Review on Halal Tourism: an Analysis on the Parameters - rahmad Hakim (Jurnal Ilmiah Ekonomi Islam, 2019)
Halal has become a global issue today, not least in Indonesia. At the state level, Indonesia is planned to become the world halal center. This is clearly seen by the Ministry of Tourism trying to increase the number of tourists visiting Indonesia, especially visiting halal tourist destinations. Some regions are trying to compete to become areas that are friendly to halal tourism, including Lombok, Aceh and finally Malang City. Regarding the halal tourism trend, it is important to know about the concepts and parameters used in implementing halal tourism. This study aims to conduct an in-depth analysis of the concept of halal tourism and several parameters that are used as standard for halal tourism destination. The method of data collection uses documentary methods based on a review of both primary and secondary literature. The results of this study are that the concept of halal tourism can be classified into two importance aspects; first, the act of obedience, which described as a way to appreciate the greatness of God’s creation. Second, the act of fulfilling an economic demand. While the parameters of halal tourism have to meet material and spiritual criteria, such as the activities have to meet shariah regulation which avoid syirk, disobedience, tabdzir or israf, and falsehood. On the other hand, the availability of services and infrastructure which meet the Muslim tourist criteria.